Recovering from the tsunami: people’s experiences in Sri Lanka - Sarvananthan, M.; Sanjeewanie, H.M.P. (Contemporary South Asia, 2008)
The present research note is based on the results of a survey conducted among the tsunami-affected communities in different regions of Sri Lanka—east, north and south (the former two are conflict-affected regions). The paper also compares and contrasts tsunami recovery efforts in other affected countries such as India and Indonesia. The major findings of the survey are that the outreach of relief has been good, that the government, donors and the civil society have not sufficiently adhered to the five cardinal principles they had agreed upon for tsunami reconstruction and recovery process in Sri Lanka, and it appears that Sri Lanka lags behind India but ahead of Indonesia in terms of quantity and quality of tsunami assistance to victims. The study also enunciates a set of proposals to improve the performance in the remaining reconstruction and recovery work to be undertaken in Sri Lanka.
Keywords: tsunami